The Impact of the Psychological and Educational Guidance Committee on the Student’s Personality within the Institute of Administration - Al-Rusafa - Mazal , Ameer Ali Hassan; Hawai , Nabaa Mohammed; Aoda , Assmahan Ahmed; Kamel , Zahraa Fadel; Hussein , Zahraa Abdul Zahra (American Journal of Biodiversity, 2024)
All the main religions provide their followers with a model of divinity. This is approachable when in the mode of attitude towards charitable action, agencies of human transformation, or when looking for the divine within the human experience. But what about other attitudes and modes of action to servanthood? What is the servant of God's place in specific religions and their ethical expectations? Any moral reestablishment involves examining the attitude towards existence and life. This issue is seen in every religion through the question of creation. How different is creation without the adopted idea of God? How is a human without the idea and possibility of becoming more of a human? The concept of the person as a created being in the image and similarity to God states the possibility to turn into an acceptable person. In the specific religious traditions, an important role should be played by the techniques of following the path of adoption and transformation. What attitudes towards existence does a person in the religious world observe? What behaviors are eliminated, directed, or imposed? Our goal is to present, in short, the concept of the servant of God in the main religions, and to argue on the matter of the implications of existence or creation, posed by different conceptions of the human in specific religious thought. What we study is man and his possibility to change. What are the necessary conditions to manage the passage from the human mode to the spiritual mode, to take home the identity card as a person?